The Effectiveness of Project-Based Learning (PjBL) Implementation Using Video Media on Student Motivation and Learning Outcomes - Ulfa; Fetri Yeni; Zelhendri Zen; Jasrial Jasrial (Postgraduate, University of Mataram, 2025)
This research was motivated by low student motivation and learning outcomes in the Culinary Basics course at SMKN 6 Padang. Conventional learning models such as lectures and PowerPoint presentations are considered incapable of generating student enthusiasm and engagement in practice-based learning. The purpose of this study was to determine the effectiveness of implementing the Project-Based Learning (PjBL) model combined with video media in improving student motivation and learning outcomes in this subject. This study used a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. Data collection used two main instruments: a learning outcome test to measure cognitive and psychomotor aspects, and a learning motivation questionnaire to measure students' affective factors. These instruments were tested for validity and reliability before use. Data were collected from two classes: an experimental class using PjBL with video media and a control class using the lecture method with PowerPoint. The results of data analysis showed a significant difference between the experimental and control classes. Students learning using the video-assisted PjBL model showed greater improvements in learning motivation and learning outcomes. The significance value obtained from the statistical test was below 0.05, indicating that the use of the video-based PjBL model was proven effective in improving the quality of culinary practical learning in vocational schools. Therefore, the implementation of video-assisted PjBL can be an innovative and engaging alternative learning strategy in vocational schools.